2020
DOI: 10.3171/2020.5.spine2062
|View full text |Cite
|
Sign up to set email alerts
|

A short-segment fusion strategy using a wide-foot-plate expandable cage for vertebral pseudarthrosis after an osteoporotic vertebral fracture

Abstract: OBJECTIVEVarious surgical treatments have been reported for vertebral pseudarthrosis after osteoporotic vertebral fracture (OVF). However, the outcomes are not always good. The authors now have some experience with combined anterior-posterior short-segment spinal fusion (1 level above and 1 level below the fracture) using a wide-foot-plate expandable cage. Here, they report their surgical outcomes with this procedure.METHODSBetween June 2016 and August 2018, 16 consecutive patients (4 male and 12 female; mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…Taiji et al reported a result of a similar procedure in 16 OVF patients and reported that the average correction loss angle was 8.5 • with one above-one below fusion [24]. The average correction loss angle in our study was 12.3 • for less than two above-two below fixation, which was larger than the study by Taiji. In their study, lamina hooks were used combined with pedicle screws, and in the patients whose kyphosis was unable to be corrected at prone position, anterior release was initially performed followed by P-A surgery, which required the patient's position to be changed twice during surgery.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Taiji et al reported a result of a similar procedure in 16 OVF patients and reported that the average correction loss angle was 8.5 • with one above-one below fusion [24]. The average correction loss angle in our study was 12.3 • for less than two above-two below fixation, which was larger than the study by Taiji. In their study, lamina hooks were used combined with pedicle screws, and in the patients whose kyphosis was unable to be corrected at prone position, anterior release was initially performed followed by P-A surgery, which required the patient's position to be changed twice during surgery.…”
Section: Discussioncontrasting
confidence: 74%
“…Recently, the widespread use of minimally invasive spinal treatment (MIST) has made it possible to perform combined anteroposterior fusion with vertebral body replacement (VBR) using a wide footplate expandable cage with a minimally invasive lateral approach [24,25]. The anterior surgical approach can be performed in the same way as the minimally invasive lumbar-lateral interbody fusion (L-LIF) approach, and corpectomy can achieve a fixation with less adjacent tissue damage [26].…”
Section: Introductionmentioning
confidence: 99%
“…Diminution and residual VAS at final follow-up were almost the same as results previously reported for OVF surgeries, including VP/BKP. [ 5 , 27 , 39 ] As for performance status, nearly 90% of patients improved by more than 1 level after surgery, with no significant difference between groups. However, the JOA score improvement ratio was significantly better in the L group (60.0%) than in the TL group (46.9%; p<0.05).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, instead of a conventional cage with a cylindrical footplate, a large rectangular footplate cage that provides coverage as wide as the vertebral endplate diameter, which may improve the mechanical supportability of the cage [ 15 , 16 ] and reduce correction losses, can be used in this surgical approach, even in patients with osteoporosis. Some surgical results have been reported [ 17 ]; however, due to the lack of comparison with the conventional anterior approach using a cylindrical cage, the effectiveness of LAVR for OVF continues to be debated.…”
Section: Introductionmentioning
confidence: 99%